Satisfacción laboral de las personas con discapacidad en el Gobierno Autónomo Descentralizado Municipal del cantón Manta - Delgado Buste, Julitza Mercedes (2025)
The purpose of this research was to analyze job satisfaction among people with disabilities in the public administration of the Gobierno Autónomo Descentralizado Municipal in Manta Canton. To this end, the study was carried out in three phases, which encompassed the procedures required to meet the specific objectives. Initially, a literature review and analysis were conducted on the employment situation and legal framework concerning people with disabilities, using bibliographic research and the deductive and analytical-synthetic methods. Subsequently, appropriate field instruments were developed. It is worth noting that the survey was designed using the Likert scale and the dimensions of the study variables. This instrument was administered to 135 people with disabilities from the institution under study. In addition, an interview was conducted with the Director of the Human Talent Department. Data tabulation and corresponding analysis were then carried out. Based on the findings obtained, a job satisfaction action plan was developed, comprising improvement strategies, which was later presented to the relevant authorities. Finally, the data collected revealed a lack of necessary training, a deficit in the recognition of individuals’ capabilities, the absence of constructive feedback, and limitations in job performance. In conclusion, this study highlights the importance of strengthening job satisfaction for people with disabilities in order to improve equal opportunity and workplace accessibility for this vulnerable group.